2015
DOI: 10.5603/ep.2014.0069
|View full text |Cite
|
Sign up to set email alerts
|

Rak kory nadnercza (ACC) — przegląd piśmiennictwa i doświadczenia własne

Abstract: Adrenocortical carcinoma (ACC) is a malignant endocrine tumour. The rarity of the disease has stymied therapeutic development. Age distribution shows two peaks: the first and fifth decades of life, with children and women more frequently affected. Although 60-70% of ACCs are biochemically found to overproduce hormones, it is not clinically apparent in many cases. If present, endocrine symptoms include signs of hypercortisolaemia, virilisation or gynaecomastia. ACC carries a poor prognosis, and a cure can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
11
0
2
Order By: Relevance
“…The number of non-severe complications of laparoscopic adrenalectomy, reaching 10%, is acceptable. Conversions to the open method are done in 5% of all cases [13][14][15]. Similar results were found in the presented study as well as in patients with malignancies and in patients with benign tumours not hormonally active.…”
Section: Rycina 2 Nowotwór Nadnerczy -Rezonans Magnetycznysupporting
confidence: 75%
“…The number of non-severe complications of laparoscopic adrenalectomy, reaching 10%, is acceptable. Conversions to the open method are done in 5% of all cases [13][14][15]. Similar results were found in the presented study as well as in patients with malignancies and in patients with benign tumours not hormonally active.…”
Section: Rycina 2 Nowotwór Nadnerczy -Rezonans Magnetycznysupporting
confidence: 75%
“…The presence of Cushing’s syndrome was confirmed on the basis of clinical evaluation in terms of clinical symptoms (altered fat distribution, wide purple striae, etc. ), assessment of 24-h urinary cortisol (normal range 12–330 nmol/24 h), serum cortisol levels after suppression test applying 1 mg dexamethasone (DXM) (immunofluorescent assay, concentrations > 140 nmol/L indicated hypercortisolism), and analysis of plasma ACTH levels (normal range 15–46 pg/mL) [41,42]. Fourteen patients had adrenal Cushing’s syndrome due to adrenal adenomas and two patients suffered from pituitary CS.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of AIs was assessed by determining UFC in 24-h urine and serum cortisol levels after suppression test with DXM using immunofluorescent assay (concentrations < 50 nmol/L excluded hypercortisolism, intermediate cut-off point of 94 nmol/L indicated subclinical hypercortisolism), dehydroepiandrosterone sulphate (DHEA-S) in serum (normal range equal to 34–430 μg/dL), aldosterone levels in serum and urine, potassium in blood, and methoxycatecholamines in 24-h urine [22,41,42]. The immunochemical assays revealed that AIs were non-hypersecretory.…”
Section: Methodsmentioning
confidence: 99%
“…patients; other causes of CS are listed in Table I [8][9][10]. Cushing's disease is more common in women, but EAS has an equal incidence in both sexes or even is more common in men.…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Ektopowe wydzielanie ACTH stanowi 10% chorych z CS, a inne przyczyny CS podsumowano w tabeli I [8][9][10]. Typowo choroba Cushinga dominuje u kobiet, natomiast CS w przebiegu EAS w równym stopniu lub częściej dotyczy mężczyzn.…”
Section: Epidemiologiaunclassified